2014
DOI: 10.1128/genomea.01134-13
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of a Moderately Halophilic Bacillus megaterium Strain, MSP20.1, Isolated from a Saltern of the Little Rann of Kutch, India

Abstract: The 4.37-Mbp draft genome of a moderately halophilic Bacillus megaterium strain, MSP20.1, isolated from a saltern of the Little Rann of Kutch, India, is reported here. To understand the mechanism(s) of moderate halophilism and to isolate the gene(s) involved in osmotolerance and adaptation, the genome of MSP20.1 was sequenced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…It has been previously reported that Bacillus megaterium possesses high levels of resistance to hostile conditions [7,8], including the exposition to metals like Hg and Ni [9,10], and some B. megaterium strains also present the demonstrated ability to remove metals from solid and liquid residues [10][11][12], establishing their potential to treat phosphogypsum waste [13], and spent catalysts [14,15]. Specifi cally, B. megaterium strain MNSH1-9K-1 presents the ability to resist up to 200 ppm of each Ni and V contained in a liquid mixture, being able to remove up to 15.38 ± 1.30 ppm of Ni contained in the former liquid medium [12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously reported that Bacillus megaterium possesses high levels of resistance to hostile conditions [7,8], including the exposition to metals like Hg and Ni [9,10], and some B. megaterium strains also present the demonstrated ability to remove metals from solid and liquid residues [10][11][12], establishing their potential to treat phosphogypsum waste [13], and spent catalysts [14,15]. Specifi cally, B. megaterium strain MNSH1-9K-1 presents the ability to resist up to 200 ppm of each Ni and V contained in a liquid mixture, being able to remove up to 15.38 ± 1.30 ppm of Ni contained in the former liquid medium [12].…”
Section: Introductionmentioning
confidence: 99%
“…It is a common model organism for a variety of cellular processes including morphology, replication, and sporulation, and it is used in industrial applications for production of recombinant proteins [11] and vitamin B12 [6,18,32]. Recently, B. megaterium has been characterized for an intrinsically high level of resistance to hostile conditions including 20 % of salinity [21,28] and metal exposition (e.g., mercury and nickel) [20,26]. Because of this capacity, B. megaterium has been used in the biological treatment of wastes with high metal content like nickel, vanadium, rhenium, and platinum [6,14,21].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, B. megaterium has been characterized for an intrinsically high level of resistance to hostile conditions including 20 % of salinity [21,28] and metal exposition (e.g., mercury and nickel) [20,26]. Because of this capacity, B. megaterium has been used in the biological treatment of wastes with high metal content like nickel, vanadium, rhenium, and platinum [6,14,21]. Particularly, nickel is considered a hazardous metal which is part of several industrial wastes, including those from petrochemical process, thus creating serious problems in terms of environmental pollution due to their accumulation [1].…”
Section: Introductionmentioning
confidence: 99%
“…Importância -Modelo em processos celulares, esporulação e lisogenia de bacteriófagos; antiviral; síntese de β-lactâmicos; resistência a antibióticos; transferência de DNA plasmidial; Giles e Reynolds 1979;Hu e Boyer, 1996;Morita et al, 1999;Vary et al, 2007;Bunk et al, 2010;Eppinger et al, 2011;Korneli et al 2013;Pal et al, 2014;Vílchez et al, 2018;Guimarães et al, 2021; Habitat -Solo; ambientes salinos; oceano; sedimentos; arrozais; mel; peixe; alimentos; Potencial -Produção de proteínas/enzimas; biossíntese vitamina B12; antifúngico; biorremediação; resistente a metais pesados; promotora de crescimento de plantas; bioinoculante;…”
Section: Bacillus Megateriumunclassified